Healing of gastric ulcers after one, two, and three months of ranitidine. Issue 6314 (13th February 1982) - Ashton, M G; Holdsworth, C D; Ryan, F P; Moore, M
Abstract : Ranitidine (150 mg twice daily) was compared with placebo in 42 patients with gastric ulcer. The study was conducted as a double-blind trial for one month, followed by an open assessment of one, two, and three months of ranitidine in the patients with persistent ulceration. Thirty-eight patients completed the double-blind trial. Repeat endoscopy confirmed complete healing in 16 of the 21 who had received ranitidine and five of the 17 who had received placebo (p less than 0.01). The remaining 17 patients with persistent ulceration participated in the open assessment. The combined cumulative healing rates of ranitidine at four, eight, and 12 weeks were 73%, 88%, and 97%. There were no adverse effects or unusual reasons for withdrawal from the study (four patients). Ranitidine appears to be a safe and highly effective treatment of gastric ulceration, with about 90% of ulcers healed after eight weeks.